Integrated system for construction companies in Cusco - Cuba Villena, Alicia (Observatorio Medioambiental, 2015)
Currently companies require innovative strategies, to manage in a comprehensive way, optimizing resources and maximizing results. Being the objective of this research work, designing an instrument of integral management (quality management, environmental, occupational health and safety) for the construction sector in Cusco. There was a current analysis of construction activity, was raised in contrast to other proposals, the design that starts with diagnosis, planning, organization, implementation, monitoring and optimization of the integrated system. The results are expressed in the diagnosis of the 3 systems, key information, for the approach and proposal of the later stages; structuring approach of subprogrammes based on a comprehensive diagnosis, to finally determine the strategic guidelines, implementation, evaluation and verification of the system, taking into account the ISO 9001: 2008, ISO 14001:2004 and OHSAS 18001:2007; as well as the current legislation for Peru.
Keywords: System; integral management; construction; Cusco.